Untargeted GC/TOFMS unravel metabolic profiles in cerebrospinal fluid of Chinese people living with HIV. Issue 3 (21st January 2021) - Keram, Alim; Pei, Ning; Qi, Tangkai; Xun, Jingna; Gu, Yutong; Li, Wenwei
Abstract: Background: Metabolic syndrome becomes a focus of clinical cares to people living with HIV (PLHIV) globally. This study aimed to explore the metabolic profiles in cerebrospinal fluid (CSF) of Chinese people living with HIV (PLHIV). Methods: Cerebrospinal fluid samples from PLHIV and healthy controls were collected from our hospital. Then, the metabolic profiles of CSFs were analyzed PLHIV with healthy individual as the normal controls using the untargeted GC/TOFMS. Following this, kyoto encyclopedia of genes and genomes annotation and pathway analysis were performed to further explore the underlying mechanism of these metabolic alterations in cognitive impairment of PLHIV. Results: Both PCA analysis and OPLS‐DA had presented that most samples were localized in 95% CI and the gap between control and HIV could significantly separate from each other. Upon this quality control, a total of 82 known metabolites were identified in CSF between PLHIV and healthy controls. Clustering of these metabolites presented that these differentially expressed metabolites could markedly distinguish HIV from healthy controls. Further pathway analyses showed that TCA cycle (citric acid, fumaric acid, lactate, et al.), amino acid (arginine, proline, alanine, aspartate, glutamine, et al.), lipid (cholesterol, butyrate, et al.) metabolisms were significantly changed in CSF of PLHIV, which might affect the cognitive status of PLHIV via affecting neuron energy support, signaling transduction, and neuroinflammation. Conclusion: Metabolic profiles were significantly altered in CSF and might play key roles in the etiology of cognitive impairment of PHLIV. Further explore the exact mechanism for these metabolic changes might be useful for cognitive impairment management of PHLIV. Abstract : CSF samples from 10 HIV‐infected patients and 10 healthy controls were collected. Then, the metabolic profiles of PLHIV CSFs were analyzed with healthy individual as the normal controls using the untargeted GC/TOFMS. Following this, KEGG annotation and pathway analysis were performed to further explore the underlying mechanism of these metabolic alterations in cognitive impairment of PLHIV.